Hormone receptor status (estrogen receptor, progesterone receptor), human epidermal growth factor-2 and p53 in South Indian breast cancer patients: A tertiary care center experience - Rashmi Patnayak; Amitabh Jena; Nandyala Rukmangadha; Amit Kumar Chowhan; K Sambasivaiah; Bobbit Venkatesh Phaneendra; Mandyam Kumaraswamy Reddy (Indian Journal of Medical and Paediatric Oncology)
Breast cancer, in India, is the second commonest cancer in females. Receptor status with ER/PR/Her 2 is now routinely done in patients with invasive carcinoma. The tumour suppressor gene, p53, is also present in most breast cancers. Proteins produced by a mutated p53 gene, accumulate in the nucleus of tumour cells and are detected by immunohistochemistry (IHC). We have undertaken this study with the aim to evaluate the ER, PR, HER-2 and p53 expressions in invasive breast carcinomas by IHC and to compare the HER-2 expression with various clinicopathological parameters. Materials and Methods: In this retrospective single institutional study from January 2001 to December 2010, 389 cases of histopathologically diagnosed infiltrating carcinoma of breast were evaluated taking into account various parameters like age, tumour size, grade, lymph node involvement, ER and PR. HER-2 and p53 was done in 352 cases. Results: The age range was 23-90 years with a mean of 50.7 years. Majority of tumours were T2 (79.6%) and Grade II (60.9%). Our data showed overall 47.6% ER, 48.8% PR, 29.6% HER-2 and 69.2% p53 positivity. There was no significant correlation between HER-2 and age, tumour size, lymph node status, ER, and PR. There was significant correlation between HER-2 and tumour grade (P = 0.031), p53 (P < 0.001). There was no inverse correlation between HER-2 and combined ER, PR status. Triple-negative breast cancers which constituted 22.7% of our cases did not reveal any correlation with various parameters. Conclusion: In our study, ER status was low, and incidence of p53 was high. These findings suggest that many of the tumours in Indian females may be of an aggressive type, and novel treatment approaches may be tried. We conclude that the assessment of all four markers is desirable.